ANALISIS KEBIJAKAN PEMERINTAH DALAM MENDORONG EKONOMI DESA DI INDONESIA - Andini Fadhila Hasibuan; Fahmil Fadillah; Rizkiyawan Wijaya; Reni Ria Armayani Hasibuan (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the effectiveness of government policies in encouraging the development of the village economy in Indonesia, with a focus on the Village Fund (Dana Desa) program and its supporting policies from 2015 to 2024. Using a qualitative approach combined with secondary data analysis and policy evaluation frameworks, this research examines the extent to which fiscal decentralization, infrastructure development, village-owned enterprises (BUMDes), and human resource capacity-building programs have contributed to economic growth, poverty reduction, and inequality decline at the village level. The findings reveal that although the Village Fund has significantly increased physical infrastructure and village economic activity, its impact on inclusive and sustainable economic growth remains limited due to uneven implementation capacity, lack of innovation in BUMDes management, and weak monitoring and evaluation systems. This study recommends policy reforms that emphasize economic empowerment based on local potential, digitalization of village governance, and stronger synergy between central and regional governments to achieve a more equitable and sustainable village economy.